Dengue diagnostics and therapeutic interventions in Viet Nam - Tricou, V; Dr Vianney M. Tricou (2011)
Dengue is a major public health problem that affects tens of millions of people annually in tropical and sub-tropical countries. This acute viral infection happens to be severe and even life threatening but there is still no available drug or vaccine. Previous studies have noted early higher viral burden in patients who develop more severe symptoms suggesting that administration of a potent and safe antiviral may prevent progression to severe dengue. To verify this hypothesis, we have conducted the first RCT directed towards reducing the viral burden in vivo by administrating chloroquine (CQ), a cheap and well-tolerated drug that inhibits DENV in vitro with concentrations achievable in vivo, to 307 Vietnamese adults with suspected dengue (257 of them were laboratory-confirmed cases). Unfortunately, we did not see an effect of CQ on the duration of infection. However in patients treated with CQ, we observed a trend towards a lower incidence of severe forms. We did not find any differences in the immune response that can explain this trend. We also found more adverse events, primarily vomiting, with CQ. In addition, we have explored the relationships between clinical features, antibody responses and virological markers in these patients. We found that the early magnitude of viremia is positively associated with disease severity and there are serotype dependent differences in infection kinetics. We found as well that DENV was cleared faster and earlier in patients with secondary infections. To complete this study, we have also evaluated 2 rapid lateral flow tests for the diagnosis of dengue in a panel of plasma samples from 245 RT-PCR confirmed dengue patients and 47 with other febrile illnesses. Our data suggest that the NS1 test component of these tests are highly specific and have similar levels of sensitivity (~60%). Both NS1 assays were significantly more sensitive for primary than secondary dengue. The IgM parameter in the SD Duo test improved overall test sensitivity without compromising specificity. All these findings are of major importance for further anti-viral drug testing.